Determination of the Prebomb Southern (Antartic) Ocean Radiocarbon in Organic Matter - Guilderson, T. P. (Lawrence Livermore National Laboratory, 2001)
The Southern Hemisphere is an important and unique region of the world's oceans for water-mass formation and mixing, upwelling, nutrient utilization, and carbon export. In fact, one of the primary interests of the oceanographic community is to decipher the climatic record of these processes in the source or sink terms for Southern Ocean surface waters in the COsub 2 balance of the atmosphere. Current coupled ocean-atmosphere modeling efforts to trace the input of COsub 2 into the ocean imply a strong sink of anthropogenic COsub 2 in the southern ocean. However, because of its relative inaccessibility and the difficulty in directly measuring COsub 2 fluxes in the Southern Ocean, these results are controversial at best. An accepted diagnostic of the exchange of COsub 2 between the atmosphere and ocean is the prebomb distribution of radiocarbon in the ocean and its time-history since atmospheric nuclear testing. Such histories of sup 14C in the surface waters of the Southern Ocean do not currently exist, primarily because there are few continuous biological archives (e.g., in corals) such as those that have been used to monitor the sup 14C history of the tropics and subtropics. One of the possible long-term archives is the scallop Adamussium collbecki. Although not independently confirmed, relatively crude growth rate estimates of A. collbecki indicate that it has the potential to provide continuous 100 year time-series. We are exploring the suitability of this potential archive.